Corrigendum to "ULF geomagnetic pulsations at different latitudes in Antarctica", published in Ann. Geophys., 27, 3621–3629, 2009 - P. Francia; P. Francia; M. De Lauretis; M. De Lauretis; M. Vellante; M. Vellante; U. Villante; U. Villante; A. Piancatelli; A. Piancatelli (Annales Geophysicae, 2010)
No abstract available.